IMPACT AND ASSESSMENT OF ILLEGAL FISHING ON RIVERINE BIODIVERSITY IN THE EASTERN CAPE, SOUTH AFRICA: A MIXED-METHODS STUDY. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background Subsistence fishing, while a livelihood source for many, significantly impacts freshwater and marine biodiversity through overexploitation and illegal practices. This study investigates the ecological and socio-economic effects of subsistence fishing, with a particular focus on the drivers and challenges of illegal fishing, despite existing regulatory efforts. Methods A mixed-methods approach was used, combining spatial analysis to identify ecologically sensitive fishing areas with quantitative survey data from 32 subsistence fishers across designated fishing zones. A structured questionnaire captured demographic profiles, fishing practices, permit status, and perceptions of fisheries regulations. Results This study confirms that illegal subsistence fishing continues to threaten biodiversity conservation, with 67% of participants acknowledging the use of unsustainable fishing methods such as gill nets and harvesting during breeding seasons. 59% of respondents were unemployed, and 72% lacked formal fishing permits. 62% were male and 38% female, with the majority citing poverty, limited alternative livelihoods, and poor policy awareness as key reasons for noncompliance. Additionally, 81% of fishers reported that they had never been engaged in community consultations or regulatory planning. Spatial mapping revealed several fishing hotspots overlapping with protected or sensitive aquatic habitats, intensifying the ecological risks. Weak enforcement, limited patrols, and a shortage of trained extension officers were cited by both fishers and local authorities as major obstacles to effective policy implementation. Conclusion Illegal subsistence fishing poses a direct threat to biodiversity, and current regulatory frameworks are inadequately enforced. Without community engagement and socio-economic support, conservation objectives are unlikely to be met. Recommendations To mitigate biodiversity loss and improve compliance, fisheries management must integrate community-based enforcement, expand awareness campaigns, and develop alternative livelihood programs. Strengthened institutional capacity and participatory governance are essential for sustainable resource use and inclusive policy outcomes.